Stress in rearing: Biochemical and growth impacts of acoustic exposure in juvenile Dicentrarchus labrax - M. Mauro; P. Giner-Tarazona; V. Espinosa; V. Puig-Pons; S. Morell-Monzó; M. Vazzana; F. Longo; R. De Luca; J. Ramis; P. Poveda; J. Carbajo; I. Pérez-Arjona (Marine Pollution Bulletin, 2026)

P06-20 Citidin Deaminase as a Predictive Biomarker of Antineoplastic Toxicity: Genotyping and Phenotyping - P. Castro-Sanchez; A. Corno Caparros; L. Pitaluga Poveda; A. Cardona Llorens; M.J. Prieto Castello; D. Marhuenda Amorós (Toxicology Letters, 2025)

P06-16 Impact of citidin deaminase genetic variants on capecitabine toxicity - P. Castro-Sanchez; A. Corno-Caparrós; L. Pitaluga-Poveda; A. Cardona-Llorens; D. Marhuenda-Amorós; M.J. Prieto-Castelló (Toxicology Letters, 2025)

Key conservation actions for European steppes in the context of the Post-2020 Global Biodiversity Framework - Cristian Pérez-Granados; Ana Benítez-López; Mario Díaz; João Gameiro; Bernd Lenzner; Núria Roura-Pascual; Julia Gómez-Catasús; Rocío Tarjuelo; Adrián Barrero; Luis Bolonio; Gerard Bota; Mattia Brambilla; et al. (Sustainability Science, 2025)
The Kunming–Montreal Global Biodiversity Framework (KM–GBF) envisions a world living in harmony with nature by 2050, with 23 intermediate targets to be achieved by 2030. However, aligning international policy and national and local implementation of effective actions can be challenging. Using steppe birds, one of the most threatened vertebrate groups in Europe, as a model system, we identified 36 conservation actions for the achievement of the KM–GBF targets and we singled out—through an expert-based consensus approach—ten priority actions for immediate implementation. Three of these priority actions address at least five of the first eight KM–GBF targets, those related to the direct causes of biodiversity loss, and collectively cover all the targets when implemented concurrently. These actions include (i) effectively protecting priority areas, (ii) implementing on-the-ground habitat management actions, and (iii) improving the quality and integration of monitoring programmes. Our findings provide a blueprint for implementing effective strategies to halt biodiversity loss in steppe-like ecosystems. Our approach can be adapted to other taxonomic groups and ecosystems and has the potential to serve as a catalyst for policy-makers, prompting a transition from political commitment to tangible actions, thereby facilitating the attainment of the KM–GBF targets by 2030.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Mycoplasma bradburyae sp. nov. isolated from the trachea of sea birds - Ana S. Ramírez; José B. Poveda; Remco Dijkman; Carlos Poveda; Alejandro Suárez-Pérez; Rubén S. Rosales; Anneke Feberwee; Michael P. Szostak; Lorenzo Ressel; Tomeu Viver; Pascual Calabuig; Salvatore Catania; et al. (Systematic and Applied Microbiology, 2023)

Global taxonomic, functional, and phylogenetic diversity of bees in apple orchards - N. Leclercq; L. Marshall; T. Weekers; P. Basu; D. Benda; D. Bevk; R. Bhattacharya; P. Bogusch; A. Bontšutšnaja; L. Bortolotti; N. Cabirol; E. Calderón-Uraga; et al. (Science of The Total Environment, 2023)

A global synthesis of the effects of diversified farming systems on arthropod diversity within fields and across agricultural landscapes - Elinor M. Lichtenberg; Christina M. Kennedy; Claire Kremen; Péter Batáry; Frank Berendse; Riccardo Bommarco; Nilsa A. Bosque‐Pérez; Luísa G. Carvalheiro; William E. Snyder; Neal M. Williams; Rachael Winfree; Björn K. Klatt; et al. (Global Change Biology, 2017)
Agricultural intensification is a leading cause of global biodiversity loss, which can reduce the provisioning of ecosystem services in managed ecosystems. Organic farming and plant diversification are farm management schemes that may mitigate potential ecological harm by increasing species richness and boosting related ecosystem services to agroecosystems. What remains unclear is the extent to which farm management schemes affect biodiversity components other than species richness, and whether impacts differ across spatial scales and landscape contexts. Using a global metadataset, we quantified the effects of organic farming and plant diversification on abundance, local diversity (communities within fields), and regional diversity (communities across fields) of arthropod pollinators, predators, herbivores, and detritivores. Both organic farming and higher in‐field plant diversity enhanced arthropod abundance, particularly for rare taxa. This resulted in increased richness but decreased evenness. While these responses were stronger at local relative to regional scales, richness and abundance increased at both scales, and richness on farms embedded in complex relative to simple landscapes. Overall, both organic farming and in‐field plant diversification exerted the strongest effects on pollinators and predators, suggesting these management schemes can facilitate ecosystem service providers without augmenting herbivore (pest) populations. Our results suggest that organic farming and plant diversification promote diverse arthropod metacommunities that may provide temporal and spatial stability of ecosystem service provisioning. Conserving diverse plant and arthropod communities in farming systems therefore requires sustainable practices that operate both within fields and across landscapes.

MiR-205 is downregulated in hereditary hemorrhagic telangiectasia and impairs TGF-beta signaling pathways in endothelial cells - Sebastien P. Tabruyn; Sylvain Hansen; Maria-Luisa Ojeda-Fernández; Nicolas Bovy; Roberto Zarrabeitia; Lucia Recio-Poveda; Carmelo Bernabéu; Joseph A. Martial; Luisa-Maria Botella; Ingrid Struman (Angiogenesis, 2013)

Protein and Antigenic Variability among Mycoplasma hyopneumoniae Strains by SDS-PAGE and Immunoblot - P. Assunção; C. De la Fe; A. S. Ramírez; O. González Llamazares; J. B. Poveda (Veterinary Research Communications, 2005)

The Occurrence of Mycoplasmas in the Lungs of Swine in Gran Canaria (Spain) - P. Assunça˜o; C. De la Fe; B. Kokotovic; O. González; J. B. Poveda (Veterinary Research Communications, 2005)